2021
DOI: 10.1590/0004-282x-anp-2020-0478
|View full text |Cite
|
Sign up to set email alerts
|

The association between intracranial pressure and optic nerve sheath diameter on patients with head trauma

Abstract: Background: Although intracranial pressure (ICP) monitoring is the gold standard method for measuring intracranial pressure after traumatic brain injury, optic nerve sheath diameter (ONSD) measurement with ultrasound (US) is also used in the evaluation of ICP. Objective: To investigate the association between a series of OSND measurements by US and changes in clinical presentation of the patient. Methods: Prospective study including 162 patients with traumatic brain injury. Age, sex, cerebral CT findings, ON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In our investigation, there was an intense inverse correlation between the patients' GCS and the mean coronal and mean axial ONSD (mm). This was supported by Çelik et al [25] who detected negative correlation between ONSD values and GSC values. Similarly, Güzeldağ et al [26] 44 adult individuals with acute middle cerebral artery stroke were shown to have an adverse link between ONSD and the GCS.…”
Section: Discussionsupporting
confidence: 63%
“…In our investigation, there was an intense inverse correlation between the patients' GCS and the mean coronal and mean axial ONSD (mm). This was supported by Çelik et al [25] who detected negative correlation between ONSD values and GSC values. Similarly, Güzeldağ et al [26] 44 adult individuals with acute middle cerebral artery stroke were shown to have an adverse link between ONSD and the GCS.…”
Section: Discussionsupporting
confidence: 63%
“…Good sensitivity and specificity in the detection of increased ICP was found, even if the cut-off values where very different among the papers. Most of the papers agreed in determining the cut-off for the presence of increased ICP when ONSD was more than 5.0 mm ( 46 49 ), whereas other suggested different values, such as 4.1 mm ( 50 ), 5.205 mm ( 51 ), 5.7 mm ( 52 ), 5.86 mm ( 53 ), 5.95 mm ( 54 ), 6.6 mm ( 55 ), and 7 mm ( 56 ).…”
Section: Resultsmentioning
confidence: 99%